The dynamics of formal employment during and after the COVID-19 pandemic in Uganda - Kyle McNabb; Tina Kaidu Barugahara; Susan Namirembe Kavuma (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This paper studies the impact of the COVID-19 pandemic on formal sector employment in Uganda. Utilizing employee-level administrative tax data from the Uganda Revenue Authority, we describe the dynamics of employment as the pandemic evolved, seeking to better understand the various coping strategies undertaken by firms in the face of reduced sales and business activity. We find that over one in ten formally employed workers fully lost their incomes in the immediate aftermath of the onset of the pandemic and associated lockdown restrictions. Of those that remained employed, some 14% saw their salaries fall in the short term (to June 2020), and by March 2021 (a full year after the onset of the pandemic) over 9% of the formal workforce were still earning less than pre-pandemic. We subsequently match these pay-as-you-earn records with firms' income tax returns to better understand how characteristics such as firm size, sector, and profitability affected the likelihood that different coping strategies were undertaken. We find that firms which were larger and more profitable pre-pandemic were more likely to retain their workforce and less likely to cut salaries throughout the course of the pandemic.
Keywords: D22; J21; J23; O12; 330; COVID-19; Uganda; formal sector employment; administrative tax data